The Word of Yahweh is right: Psalm 33 as a Torah-psalm - Phil J. Botha; J. Henk Potgieter (Verbum et Ecclesia, 2010)
This article investigates some of the similarities between the Torah-psalms and Psalm 33. It is suggested that the Torah-psalms should be re-contextualised and understood as part of a post-exilic endeavour to provide an interpretation of the emerging canon of Hebrew scripture for the faithful of the late Persian period. Psalm 33 can also be counted amongst the literary products of this endeavour. The service it rendered to its audience was to establish a connection between Yahwehs work of creation, his redemption of Israel and his divine rule over all the world through the power of his word.